Role of visual function and performance of activities of daily living in cognitive function in patients with mild cognitive impairment: a cross-sectional study - Chunhui Zhou; Ganfeng Yang; Marc Theeboom; Hua Yang; Ruiting Zhu; Zijian Zhou; Dong Zhu (Frontiers in Aging Neuroscience)
BackgroundMild cognitive impairment (MCI) is a precursor to dementia, with many patients showing early decline in activities of daily living (ADLs). However, the role of visual impairment in this process is underexplored despite evidence suggesting it may accelerate cognitive decline. Current research does not understand how visual dysfunction affects cognitive abilities and how ADLs might moderate this relationship. This gap is crucial because early interventions targeting visual impairments could potentially delay progression to dementia, offering new avenues for supporting MCI patients.ObjectiveThis study investigates the relationship between visual function and cognitive abilities in patients with MCI. Specifically, it seeks to determine how different aspects of visual function, such as visual field indices and visual acuity, correlate with various cognitive domains measured by standardized assessments. Additionally, the study aims to examine the role of ADLs as a potential moderating factor in this relationship. By analyzing how ADL performance influences the strength and direction of the association between visual impairments and cognitive function, this research intends to identify key areas where visual deficits may contribute to cognitive decline in MCI.MethodsThis is a cross-sectional study. Two hundred and seventy four elderly patients were diagnosed with MCI from various communities in Taicang City, Jiangsu Province, China. Most participants were women (68.6%), and the average age was 69 years. Notable comorbidities included hypertension (41.6%) and diabetes (33.2%), indicating a higher burden of health conditions than typical older adult populations. Visual function, Montreal Cognitive Assessment (MoCA), and the ADLs were measured. Pearson's correlation coefficients were used to examine the unadjusted associations between visual function measures and cognitive performance. Multivariable linear regression models were employed to further explore these relationships and to assess the moderating role of ADLs.ResultsSignificant positive correlations were found between visual function and cognitive performance, particularly with Visual Function Index (VFI) showing a strong initial correlation with the total MoCA score (r = 0.61, p < 0.001), which was attenuated after adjusting for ADL (β = 0.06, p = 0.23). Maximum Visual Field (Max VF) was positively correlated with language skills (r = 0.13, p < 0.05). The negative correlation of Minimum Visual Field (Min VF) with cognitive performance became positive after ADL adjustment (β = 0.12, p = 0.04).ConclusionsThese findings suggest that visual function plays a crucial role in the cognitive and functional abilities of patients with MCI. Early interventions targeting visual impairments may help mitigate cognitive decline and improve the quality of life for these patients.